Evaluating Medication Errors for inpatients: The Jordanian experience - Sulaiman, Zena; Hamadi, Salim; Obeidat, Nathir; Basheti, Iman (Jordan Journal of Pharmaceutical Sciences, 2021)
Objective: To investigate the rate, frequency, and severity of medication errors detected by a clinical pharmacist at a teaching hospital in Amman, Jordan. Secondly, to determine the risk factors associated with the occurrence of these errors. Method: This prospective study used two methods of medication error detection. Direct observation and the chart review method. Both methods were conducted in the internal medicine ward between June and December 2013. In the selected shifts, all processes performed on the in patients were observed and recorded by the clinical pharmacist. The number and types of medication errors were documented. Risk factors associated with more errors were then explored. All collected data was entered into SPSS and analyzed accordingly. Results: During the period of the study, a total of 803 medication errors per 6396 opportunities for errors (12.6%) were documented. Of those, there were 739 (20.2%) administration errors, 40 (1.5%) transcription errors, 21 (0.8%) dispensing errors and 3(0.1%) prescribing errors. Risk factors associated with the total number of detected medication errors were mainly shorter nurse’s experience in the ward (R2=0.456, p< 0.042) and patients with higher number of prescribed doses (R2=0.451, p< 0.025). Conclusion: This study revealed that medication errors happening in a teaching hospital occur mainly during the administration and transcription stages of the medication use process. Shorter nurse experience can lead to a higher rate of medication errors. Raising the medical staff awareness regarding medication errors, mainly for patents with a high number of prescribed doses, can lower the rate of medication errors.